Perception about tooth colour and appearance among patients seen in a tertiary hospital, SouthWest, Nigeria (2021)
Introduction: patients´ satisfaction with their dental appearance and tooth colour is often influenced by certain factors which need to be addressed periodically among different populations. Methods: a self-administered questionnaire consisting of sociodemographic data, questions on patients´ satisfaction with tooth colour, perceived malalignment of teeth, nonaesthetic anterior tooth-coloured restoration and presence of tooth fracture were distributed. Data collected was analysed using Statistical Package for Social Sciences (IBM, SPSS version 20). Chi square was used to test the statistical differences at a significance of p> 0.05. Results: a total of 410 patients (M=147, F=263) participated in the study. About 73% had tertiary education while 36.3% were within the modified ISCO-08 Group 2. The respondents that were satisfied with the general dental appearance and tooth shade were 66.3% and 63.5% respectively. More males (65.1%) than females (62.7%) were satisfied with tooth colour while more females (69.1%) were satisfied with dental appearance. The older age group were more satisfied with dental appearance and tooth colour. Awareness of tooth whitening (Over 80%) and the desire to undergo tooth whitening was more among the post-secondary individuals. More of dental patients (73.1%) than medical (59.2%) were satisfied with teeth appearance (p=0.003). Conclusion: patients are increasingly aware of their dental appearance/tooth colour and the need to improve it with tooth bleaching and/or orthodontic treatment. Female were more dissatisfied with their tooth colour but more satisfied with their dental appearance than the male. Older people were more satisfied with their dental appearance and tooth colour compared to younger age group